Culture, church, and collective: a qualitative study about gambling harm prevention and reduction in Aotearoa/New Zealand-a Tongan male perspective - Edmond S. Fehoko; Maria E. Bellringer; Peggy Fairbairn-Dunlop (BMC, 2022)
Abstract Background In New Zealand, Pacific people continue to be more at risk of gambling harm than the general population, despite increasing public health efforts and treatment service provisions introduced to address this social and health issue. In looking at why this is so, our first concern was to ask why the delivery of the prevailing gambling-focussed programmes was not influencing Pacific gambling behaviours. In seeking to answer this question, it was important to explore ethnic-Pacific-specific factors of gambling harm prevention and reduction. Methods The research design was interpretivist/constructivist and phenomenological, applied through the lens of a Tongan worldview. Participants comprised Tongan male elders and youth. Recruitment of participants was through snowball sampling from churches and kava-drinking circles. A total of 28 elders and 18 youth participated through focus group talanoa and individual talanoa. This study employed descriptive thematic analysis. Results Participants were not aware of any policy document or problem-gambling preventative programmes. Four key themes were raised, which include raising the awareness of existing gambling harm treatment providers, the church influence in addressing gambling harm, community-based strategies, and cultural-based approaches. Conclusions This study proposes several recommendations such as more awareness of gambling harm providers in community, increasing cultural spaces and church engagements, and calls for further research in addressing the prevention and reduction of gambling harm amongst the Tongan community in New Zealand.